Oncoimmunology Meets Organs-on-Chip - Mattei, Fabrizio; Andreone, Sara; Mencattini, Arianna; De Ninno, Adele; Businaro, Luca; Martinelli, Eugenio; Schiavoni, Giovanna (Frontiers in Molecular Biosciences, 2021)
Oncoimmunology represents a biomedical research discipline coined to study the roles of immune system in cancer progression with the aim of discovering novel strategies to arm it against the malignancy. Infiltration of immune cells within the tumor microenvironment is an early event that results in the establishment of a dynamic cross-talk. Here, immune cells sense antigenic cues to mount a specific anti-tumor response while cancer cells emanate inhibitory signals to dampen it. Animals models have led to giant steps in this research context, and several tools to investigate the effect of immune infiltration in the tumor microenvironment are currently available. However, the use of animals represents a challenge due to ethical issues and long duration of experiments. Organs-on-chip are innovative tools not only to study how cells derived from different organs interact with each other, but also to investigate on the crosstalk between immune cells and different types of cancer cells. In this review, we describe the state-of-the-art of microfluidics and the impact of Organs-on-chip in the field of oncoimmunology underlining the importance of this system in the advancements on the complexity of tumor microenvironment.